Implementation of Notary Public Liability against Authentic Deed Made According to Act No. 2 of 2014 Concerning Amendments to Act No. 30 of 2004 Regarding Notary Position - Zahren Zukri Alyafie; Amin Purnawan (Sultan Agung Notary Law Review, 2021)
This study aims 1) To find out the implementation of the Notary Public Responsibilities on the Authentic Deed made according to Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning Notary Position in Kendari City; 2) To find out obstacles and solutions in the Implementation of Notary Responsibilities for the Authentic Deed he made in Kendari City. This study uses an empirical juridical approach, the specification of this research is descriptive analytical. Types of data in this study include primary data and secondary data. Data obtainedwith the method of interview and literature study.The data analysis technique is qualitative. Based on this research it is concluded that: 1)Implementation of Civil Notary Responsibilities for the Authentic Deed that he makes, the notary is only responsible for the formal correctness of an authentic deed and not for the material of the authentic deed. The legal basis used in civil liability for deeds made by the Notary is if the Notary makes a mistake due to broken promises as determined in the provisions of Article 1234 of the Civil Code and acts against the law as stipulated in the provisions of Article 1365 of the Civil Code.2) Barriers and Solutions in the Implementation of Notary Responsibilities for the Authentic Deed that he makes, namely: a) Obstacles in Implementing the Notary's Responsibility towards the Authentic Deed that he makes, if one of the parties then feels that someone has been harmed, in this case it is the responsibility of the parties, not the responsibility of the notary. In fact, deeds made by notaries are evidence that the parties can use. b) Solutions in the Implementation of Notary Responsibilities for the Authentic Deed He Made If it is proven that there is a violation committed by the notary concerned and it is detrimental to one of the parties because of the deed he made. Regarding the civil claim, the notary concerned is obliged to compensate for the civil loss if proven.